Chile’s experience for modern Ukraine - Kazakova, Nadezhda; Koniaieva, Yelyzaveta (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2018)
The paper defines status and development trends in the Chilean economy as a subject of the world economy, the place of the country in the world economic system and integration of Chile into the world economy. Recently the political cooperation between Ukraine and Chile has been supplemented by the economic one. Both states are interested in cooperation in different spheres of the economic activity. The paper reveals the prospects for the development of foreign trade of Chile, as well as determines the effectiveness of the Ukrainian-Chilean economic cooperation. The study gives foreign trade development prospects of Ukrainian-Chilean economic relations. The author offers methods how to develop Ukrainian-Chilean economic relations